Challenges of the Muslim world present, future and past - Yue, Piyu (International symposia in economic theory and econometrics ;, 2008)
This book provides a data-based approach to present and future developments in the Muslim world. This is an unusual approach to this topic that highlights important underlying forces in current and projected future economic and social behaviour that range from prices of gasoline to terrorism and related activities. In the context of the rich histories of Muslim cultures, the effects of rapid changes in economic and social trends are examined, as well as the effect of Western policies which have often exacerbated underlying tensions in these fast-growing populations, extending to the trouble and hostilities that are currently being manifested in proposed interpretations by al-Qaeda and similar organizations. This volume also suggests an approach that deals with the high illiteracy rates and inadequate education facilities in many Muslim countries.It is a new volume in the established ISETE series. It focuses on the economics of the Muslim world, including hot topics such as terrorism and oil-prices.